2010
DOI: 10.1080/15228932.2010.481233
|View full text |Cite
|
Sign up to set email alerts
|

Formalizing Clinical Decisions in Individual Treatments: Some First Steps

Abstract: A fundamental problem in forensic psychology practice is the lack of formal statistical methods to support team decisions about an individual patient's progress during intramural treatment. It is common practice to base decisions about the progress of a treatment on subjective clinical impressions of therapists. In this article, an approach is proposed that can be seen as a contribution to bridge the gap between formal statistical decision making and subjective clinical decision making. To formalize decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Before filling out the IFTE, the main clinician gives his/her clinical judgment whether he/she thinks the behavior of a patient has changed by answering the question: “Has the patient changed in this last period?” A 13-pointscale with four anchor points is used: 0 = “worsened,” 1 = “no change,” 2 = “a little improved” and 3 = “a lot improved.” Main clinicians in this institution are the coordinators of the treatment and are mostly (clinical) psychologists. The information is displayed in a treatment evaluation report in which the average team score per item and per factor are displayed as well as a measurement of change (Spreen et al, 2010) and a team agreement index per item (Gower & Legendre, 1986) is reported. The agreement index (0.00 is no agreement, 1.00 is total agreement) displays whether the behavior is consistently observed in different situations by different therapists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before filling out the IFTE, the main clinician gives his/her clinical judgment whether he/she thinks the behavior of a patient has changed by answering the question: “Has the patient changed in this last period?” A 13-pointscale with four anchor points is used: 0 = “worsened,” 1 = “no change,” 2 = “a little improved” and 3 = “a lot improved.” Main clinicians in this institution are the coordinators of the treatment and are mostly (clinical) psychologists. The information is displayed in a treatment evaluation report in which the average team score per item and per factor are displayed as well as a measurement of change (Spreen et al, 2010) and a team agreement index per item (Gower & Legendre, 1986) is reported. The agreement index (0.00 is no agreement, 1.00 is total agreement) displays whether the behavior is consistently observed in different situations by different therapists.…”
Section: Methodsmentioning
confidence: 99%
“…Main clinicians in this institution are the coordinators of the treatment and are mostly (clinical) psychologists. The information is displayed in a treatment evaluation report in which the average team score per item and per factor are displayed as well as a measurement of change (Spreen et al, 2010) and a team agreement index per item (Gower & Legendre, 1986) is reported. The agreement index (0.00 is no agreement, 1.00 is total agreement) displays whether the behavior is consistently observed in different situations by different therapists.…”
Section: Instrumentmentioning
confidence: 99%
“…To offer more insight into the individual responses of patient, the treatment was also tested employing an additional N = 1 statistical approach as discussed in Spreen, Timmerman, Horst, and Schuringa (2010). This specific N = 1 approach is developed to support decisions about an individual patient’s progress during treatment and can also be employed to test the effect of an individual therapy.…”
Section: Methodsmentioning
confidence: 99%
“…In intervention studies on complex human behavior in the field of, for example, social work (Wong, 2010), forensic psychology (Spreen et al, 2010), special education (Horner et al, 2005), and counseling practices (Lenz, 2015), Single Case Research (SCR) has been applied. SCR is a viable alternative when between-group studies, such as Randomized Controlled Trials (RCTs), are not possible (Hein & Weeland, 2019).…”
Section: Introductionmentioning
confidence: 99%